2017
DOI: 10.12659/msm.904824
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Atrial Fibrillation by Using Sarcoplasmic Reticulum Calcium ATPase Pump Overexpression in a Rabbit Model of Rapid Atrial Pacing

Abstract: BackgroundRecent research suggests that abnormal Ca2+ handling plays a role in the occurrence and maintenance of atrial fibrillation (AF). Therefore, Ca2+ release and ingestion depend on properties of the ryanodine receptor (RyR) and sarcoplasmic reticulum Ca2+ATPase2a (SERCA2a). This study aimed to detect whether SERCA2a gene overexpression has a preventive effect on atrial fibrillation caused by rapid pacing right atrium.Material/MethodsForty-eight New Zealand white rabbits were randomly divided into a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…AERP and AF inducibility were measured as described in our previous study (Wang et al, 2017). AERP was conducted with a programmed train of eight basic stimuli (S1-S1 = 260 ms) followed by one extra stimulus (S2) with an initial pacing length of 200 ms and 5 ms decrements until S2 failed to capture the depolarization.…”
Section: Electrophysiological Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…AERP and AF inducibility were measured as described in our previous study (Wang et al, 2017). AERP was conducted with a programmed train of eight basic stimuli (S1-S1 = 260 ms) followed by one extra stimulus (S2) with an initial pacing length of 200 ms and 5 ms decrements until S2 failed to capture the depolarization.…”
Section: Electrophysiological Measurementmentioning
confidence: 99%
“…The atrial tissue was sliced into 5 µmthick cross-sections to visualize the cell structure. The sections were deparaffinized and subjected to hematoxylin and eosin (H&E) staining, Masson's trichrome staining, and picrosirius red staining for assessment of basic tissue structure and detection of fibrosis following the methods of our previous study (Wang et al, 2017). Digital photographs were taken under a Leica microscope (DM2500, Wetzlar, Germany).…”
Section: Histological Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…LV tissues were cut into small pieces, fixed with 4% paraformaldehyde, and embedded in paraffin. Hematoxylin-eosin (HE) staining, Masson's trichrome staining, and picrosirius red staining were performed on the 5 μ m thick histological sections to analyze LV fibrosis in the light of our previous method [ 23 ]. Eight paraffin blocks per group were taken for the tissue slide preparation and 9 separate bright field microscopic images per animal were quantified.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, in patients with a preserved ejection fraction and AF, the content of SERCA2a in the right atrial myocardium was significantly lower than in patients without rhythm disturbances [7]. Experimental studies have shown that modeling both acute and chronic AF leads to a decrease in the expression of SERCA2a, while overexpression of this protein reduces the AF occurrence rate [8][9][10]. In addition, since the functioning of SERCA2a is associated with significant energy consumption [11], under the conditions of a high frequency of atrial contraction, cardiomyocytes may lack energy supply, which may lead to a decrease in both activity and expression of this protein.…”
mentioning
confidence: 99%